Caracterización biológica y hábitos de la mosca del botón floral Dasiops saltans (Townsend, 1913) en el cultivo de pitahaya amarilla Selenicereus megalanthus, 1953 - López Cruz, Eduardo Enrique (2022)
In context, the present work was developed with the purpose of gathering information on the biology and main characteristics of the flower bud fly Dasiops saltans Townsend in the yellow pitahaya crop. This insect is the most economically important pest in yellow pitahaya, causing losses in flowering that can vary between 40 and 80%. The bases of integrated pest management are very few, and farmers devote their control efforts to the use of chemical synthesis products with consequences that result in pest resistance. The aim is to use the information generated to propose possible control methods for this pest, which will help growers to make the crop profitable and avoid the indiscriminate use of agrochemicals. The healthy flower buds of yellow pitahaya are green in color. On the other hand, flower buds affected by D. saltans can be recognized in the field by their reddish coloration. D. saltans is generally present during the flowering period, attacking the flower buds of yellow pitahaya which is the only known host. The yellow pitahaya Selenicereus megalanthus is a crop that is gaining importance in Ecuador, due to its condition of being a non-traditional crop, and with a high export potential. In recent years, it has become an agricultural fruit product of high commercial value in Ecuador, becoming one of the main producers of pitahaya along with Colombia and Israel.